UAV-Based Smart Educational Mechatronics System Using a MoCap Laboratory and Hardware-in-the-Loop - Luis F. Luque-Vega; Emmanuel Lopez-Neri; Carlos A. Arellano-Muro; Luis E. González-Jiménez; Jawhar Ghommam; Maarouf Saad; Rocío Carrasco-Navarro; Riemann Ruíz-Cruz; Héctor A. Guerrero-Osuna (Sensors, 2022)
Within Industry 4.0, drones appear as intelligent devices that have brought a new range of innovative applications to the industrial sector. The required knowledge and skills to manage and appropriate these technological devices are not being developed in most universities. This paper presents an unmanned aerial vehicle (UAV)-based smart educational mechatronics system that makes use of a motion capture (MoCap) laboratory and hardware-in-the-loop (HIL) to teach UAV knowledge and skills, within the Educational Mechatronics Conceptual Framework (EMCF). The macro-process learning construction of the EMCF includes concrete, graphic, and abstract levels. The system comprises a DJI Phantom 4, a MoCap laboratory giving the drone location, a Simulink drone model, and an embedded system for performing the HIL simulation. The smart educational mechatronics system strengthens the assimilation of the UAV waypoint navigation concept and the capacity for drone flight since it permits the validation of the physical drone model and testing of the trajectory tracking control. Moreover, it opens up a new range of possibilities in terms of knowledge construction through best practices, activities, and tasks, enriching the university courses.